Event Deposits: The Role of Sediment Supply and Relative Sea-level Changes - Overview - G. Einsele (Berita Sedimentologi, 1998)
This overview on event deposits is based on (1) a brief summary on denudation rates in regions of various relief and climate as derived from the suspended and bed loads of river, (2) the fractions of sand and mud present in the filld of various basins, and (3) the mechanisms controlling sediment remobilization.